2016
DOI: 10.1088/1752-7155/10/4/046011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red dyes on blue light phototoxicity against VSC producing bacteria in an experimental oral biofilm

Abstract: Oral malodour is considered to be caused mainly by the production of volatile sulfide compounds (VSC) by anaerobic Gram-negative oral bacteria. Previous study showed that these bacteria were susceptible to blue light (wavelengths of 400-500 nm). In the present study, we tested the effect of blue light in the presence of red dyes on malodour production in an experimental oral biofilm. Biofilms were exposed to a plasma-arc light source for 30, 60, and 120 s (i.e. fluences of 41, 82, and 164 J cm, respectively) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Among the two PS tested, RB was found to be more effective than ERY. This result is in agreement with other studies evaluating the antimicrobial effectiveness of aPDI mediated by xanthene dyes (e.g., RB, eosin Y, ERY) [ 26 , 56 , 57 , 58 ]. This finding may be attributed to the capacity of RB in producing singlet oxygen with a quantum yield of nearly 100% due to the number of iodide substituents in the xanthene ring under irradiation [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among the two PS tested, RB was found to be more effective than ERY. This result is in agreement with other studies evaluating the antimicrobial effectiveness of aPDI mediated by xanthene dyes (e.g., RB, eosin Y, ERY) [ 26 , 56 , 57 , 58 ]. This finding may be attributed to the capacity of RB in producing singlet oxygen with a quantum yield of nearly 100% due to the number of iodide substituents in the xanthene ring under irradiation [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that sub-lethal dosage of blue light can increase cell membrane permeability in Fusobacterium nucleatum [13,14] and suggested that this effect was mediated through the production of reactive oxygen species [11]. In the present study, we tested the combined effect of sub-lethal blue light and silver nanoparticles on the ability of Fusobacterium nucleatum to produce malodor, its cell membrane integrity, and measured the levels of ROS produced following this treatment in order to understand the mechanism for the combined phototoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the phototoxic effect of blue light against malodor producing bacteria [10] with or without the added effect of photosensitizers [11] or photoactivators [12]. Furthermore, the main antibacterial mechanism of blue light against Fusobacterium nucleatum was shown to be membrane damage [13] that could be leveraged to increase the efficacy of other antibacterial agents [14].…”
Section: Introductionmentioning
confidence: 99%